Freedom: a Matter of Choice and Action (Papeles, 2012)
In this Article of critical remark is rescued a concept of freedom which has been suggested by the heterodox economist Albert Hirschman (2002). This author affirmed that freedom is a choice about styles of life (moral values, ideologies and meta-preferences) and this hard election implies will and actions: exit from inherited institutions and everyday choices (tastes and preferences) and, moreover, fight against social order.